Application of Bionics in Wing Design of Aerospace Vehicles - Feng, Yilong (Transactions on Environment, Energy and Earth Sciences, 2024)
With the rapid development of aviation technology, the requirements for aircraft performance are getting higher and higher, and traditional aircraft design is facing numerous challenges. Bionics provides new ideas and solutions for the development of aviation technology by imitating the structural and functional principles of natural organisms. In this paper, the limitations of traditional aircraft wings are first analyzed and the ideas of bionics in improving wing design are discussed. Then, it discusses the research progress in morphology bionics, structure bionics, function enhancement, and material innovation. The potential of bionics to improve the performance of aircraft, reduce energy consumption, and enhance stability is demonstrated. Through the integrated application of morpho-bionics, structural bionics and functional bionics, researchers have not only solved the shortcomings of conventional wings but also significantly improved the aerodynamic performance and flight efficiency of aircraft. This paper aims to provide useful references and inspirations to promote the innovation and development of aeronautics technology.